2018
DOI: 10.1080/17439760.2018.1484941
|View full text |Cite
|
Sign up to set email alerts
|

How WEIRD are positive psychology interventions? A bibliometric analysis of randomized controlled trials on the science of well-being

Abstract: The past two decades have witnessed a rapid rise in well-being research, and a profusion of empirical studies on positive psychology interventions (PPIs). This bibliometric analysis quantifies the extent to which rigorous research on PPIs that employ randomized controlled trials (RCTs) reaches beyond Western Educated Industrialized Rich Democratic (WEIRD) populations. A search was conducted through databases including PubMed, PsycINFO, and Scopus for studies from 1998 to 2017. In total, we found 187 full-text … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(135 citation statements)
references
References 79 publications
5
112
0
6
Order By: Relevance
“…Differences in effect sizes between Western and non-Western countries are possibly confounded by study quality, because six of the ten low-quality studies on depression were from non-Western countries. The findings in relation to the lower quality of studies from non-Western countries and possible large effect sizes are in line with a meta-analysis that we recently conducted on the efficacy of PPIs from non-Western countries (Hendriks et al 2018b). This study, that included 28 RCTs, showed that PPIs from non-Western countries have moderate effect sizes on well-being, and large effects on depression and anxiety.…”
Section: Main Findingssupporting
confidence: 87%
See 1 more Smart Citation
“…Differences in effect sizes between Western and non-Western countries are possibly confounded by study quality, because six of the ten low-quality studies on depression were from non-Western countries. The findings in relation to the lower quality of studies from non-Western countries and possible large effect sizes are in line with a meta-analysis that we recently conducted on the efficacy of PPIs from non-Western countries (Hendriks et al 2018b). This study, that included 28 RCTs, showed that PPIs from non-Western countries have moderate effect sizes on well-being, and large effects on depression and anxiety.…”
Section: Main Findingssupporting
confidence: 87%
“…The positive psychology movement intended to redirect the course of psychological research: away from a focus on pathology, diseases and deficits, and towards the study of human strengths, flourishing and the optimal functioning of individuals, groups, and institutions (Gable and Haidt 2005;Seligman and Csikszentmihalyi 2000;Sheldon and King 2001). Since its inauguration in 1998, the movement has made a considerable impact on the scientific community, with an exponential growth of publications (Donaldson et al 2015;Hart and Sasso 2011;Hendriks et al 2018b;Kim et al 2018;Rusk and Waters 2013). Positive psychology builds on the ideas of humanistic psychology, but employs state-of the art-research methods to ensure scientific rigor (Froh 2004;Sheldon and Kasser 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The general lack of studies from non-Western countries is a concern that has been voiced by many scholars in the field of cross-cultural psychology (Berry, 2013;Henrich, Heine, & Norenzayan, 2010;Jahoda, 2016;Marsella & Yamada, 2010;Owusu-Bempah & Howitt, 2000). However, it appears that the increase in the number of studies within the growing field of positive psychology is not only limited to publications originating from Western countries; a quarter to a third of the studies in the field of positive psychology now originate from non-Western countries (Donaldson, Dollwet, & Rao, 2015;Hendriks et al, 2018b;Kim, Doiron, Warren, & Donaldson, 2018). A recent systematic review and meta-analysis on the efficacy of positive psychology intervention (PPIs) from non-Western countries that included 28 randomized controlled trials (RCTs) reported that effect sizes of studies from such countries were considerably higher than those from Western countries (Hendriks et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Positive Massage (PM) is a health intervention, aiming to enhance interpersonal and intrapersonal wellbeing in close relationships through mutual lay massage [40] [41]. Instead of lengthy clinical professional massage therapy, PM has been created to be a self-help technique 3 , with a short (15 min) sequence of massage to be used in a home environment 4 The intention of PM is not to replace professional massage therapy, but to increase self-care skill as a preventative activity which may also enhance massage therapy effects by professionals. PM would be well suited to complement professional massage therapy for those who seek a health remedy.…”
Section: Positive Massagementioning
confidence: 99%
“…Although positive psychology has been globally advancing evidential studies in wellbeing [3], the focus has been strongly on an individual approach [4] [5].…”
Section: Introductionmentioning
confidence: 99%